[Comment on] Fitzgerald, E.V.K. Private sector investment and savings behavior: the policy implications of capital account disaggregation - Malik, Sohail (Pakistan Institute of Development Economics, 1992)
After a prolonged period of macroeconomic adjustment, lasting at least a decade in most LDCs, much has been learned (and in many cases re-learned) and a consensus reached about many key policy points, such as the virtues of budgetary balance, the need for a strong real exchange rate, and the requirement for microeconomic reforms if markets are to work properly. To a considerable extent, moreover, there has been success in closing current account deficits, reducing government expenditure and moderating rates of inflation. Much of this logic is reflected in the standard policy models employed by the Bank and the Fund which I shall discuss today. However, to the extent that macroeconomic adjustment is intended to lead on to renewed growth (and eventually poverty alleviation) the debate is far less consensual. Two main lines of critique have been directed at what can be called the 'Washington Consensus': The first suggests that macroeconomic adjustment - as theorised and practised - has had negative effects in terms of employment, income distribution and even the environment, particularly because of the reduction in real wages and key public expenditures. The second line of dissent from the standard model stresses the deleterious effect of orthodox macroeconomic adjustment packages on output growth itself, both through unnecessarily severe demand reductions on the one hand, and excessive adjustments (upward) to real interest rates and (downward) to public investment levels without taking into account the domestic implications of external debt positions.